A Study of Javanese Female EFL Learners’ Politeness in Request Speech Acts - Cahyaningrum, Dewi; Yulianti, Andi Indah; Setyowati, Ratini; Nababan, Mangatur (Program Studi Pendidikan Bahasa Program Pascasarjana Universitas Negeri Jakarta, 2025)
This study explores the request strategies of Javanese female English as a Foreign Language (EFL) learners and how these reflect their politeness in communication. It examines the influence of Javanese cultural values and gender on their choice of strategies. Using Trosborg's (1994) request categorization and Brown and Levinson's (1987) politeness theory, data were collected through role-play and semi-structured interviews. The analysis identifies that the learners mainly use conventionally indirect strategies, particularly hearer-oriented ones, with negative politeness being the most common approach. These strategies emphasize indirect phrasing and respect for the listener's autonomy. Javanese cultural values, such as humility (andhap asor) and empathy (tepa selira), significantly shape these choices. Gender norms also play a role, encouraging politeness and indirectness to reduce imposition and promote harmony. The findings suggest that integrating cultural awareness and contextually appropriate strategies into English teaching can help learners communicate effectively in formal or professional settings